Improving teenagers' knowledge of emergency contraception: cluster randomised controlled trial of a teacher led intervention. Issue 7347 (18th May 2002) - Graham, Anna; Moore, Laurence; Sharp, Deborah; Diamond, Ian
Abstract: Objective: To assess the effectiveness of a teacher led intervention to improve teenagers' knowledge about emergency contraception. Design: Cluster randomised controlled trial. Setting: 24 mixed sex, state secondary schools in Avon, south west England. Participants: 1974 boys and 1820 girls in year 10 (14-15 year olds). Intervention: Teachers gave a single lesson on emergency contraception to year 10 pupils. The teachers had previously received in-service training on giving the lesson. The pupils were actively involved during the lesson. Main outcome measures: Questionnaires distributed to pupils at baseline and six months after the intervention assessed their knowledge of the correct time limits for hormonal emergency contraception and for use of the intrauterine device as emergency contraception, the proportion of pupils who were not virgins, the proportion who had used emergency contraception, and the pupils' intention to use emergency contraception in the future. Results: The proportion of pupils knowing the correct time limits for both types of emergency contraception was significantly higher in the intervention group than in the control group at six months' follow up (hormonal contraception: proportion of boys 15.9% higher (95% confidence interval 6.5% to 25.3%), girls 20.4% (10.4% to 30.4%); intrauterine device used as emergency contraception: boys 4.2% (0.7% to 7.7%), girls 10.7% (0.4% to 21.0%). The number of pupils needed to be taught for one more pupil to know the correct time limits was six for boys and five for girls. The intervention and control groups did not differ in the proportion of pupils who were not virgins, in the proportion who had used emergency contraception, and in the proportion intending to use emergency contraception in the future. Conclusions: The intervention significantly improved the proportion of boys and girls knowing the correct time limits for both types of emergency contraception. The intervention did not change the pupils' sexual activity or use of emergency contraception.